(untitled) (Research, Society and Development, 2021)
Objective: to describe the screening process in transsexual women with cancer undergoing vaginoplasty and the associated risk factors. Methodology: systematic review carried out in national and international databases, with descriptors transgender, neovagina , neoplasm, cancer and carcinoma, articulated by the AND and OR rounders, which generated the final selection of 7 international articles. Results: It was evidenced that transsexual women used the technique with penile and scrotal tissue, aged over 43.75 years and surgery time between 20 and 40 years of surgery. All had squamous cell adenocarcinoma, most of which were associated with papillomavirus infection. Among the pelvic symptoms found, pain, bloody secretion and foul smelling stand out, and the detection of a tissue mass in the introitus and inside the neovagina. The exams were collected through biopsy or smear for cytopathological analysis and microbiological testing. Final considerations: Periodic evaluation of redesignated transsexual women is necessary in order to promote sexual health and the prevention or early detection of neovaginal neoplasia.